Intravenous immunoglobulin protects from experimental allergic bronchopulmonary aspergillosis via a sialylation‐dependent mechanism. Issue 1 (29th October 2018) - Bozza, Silvia; Käsermann, Fabian; Kaveri, Srini V; Romani, Luigina; Bayry, Jagadeesh
Abstract : Intravenous immunoglobuin (IVIG) exerts protective effects in experimental allergic bronchopulmonary aspergillosis (ABPA) via a sialylation‐dependent mechanism. The protection was associated with reduced recruitment of eosinophils, diminished goblet cell hyperplasia, suppressed Th2 and Th17 responses and reciprocally enhanced regulatory T cells and IL‐10, and decreased IgE levels in the circulation.